Plant-Based Foods: Safety Risks and Countermeasures - ZHU Lei, LIU Jing, XU Huan, PAN Yingjie, ZHAO Yong, ZHANG Zhaohuan (Shipin Kexue)
Plant-based foods, a new category of foods made from plant materials with specific processes, have characteristics similar to those of animal-based foods, which meet consumers’ nutritional needs. Plant-based foods have become a research hotspot and key focus in the field of food science, as they help to ensure sustainable food supply, realize efficient and low-carbon utilization of resources, and promote the optimization of residents’ dietary structure and the improvement of nutritional levels. At present, most research on plant-based foods focuses on developing new products, but little attention has been paid to potential food safety risks. In order to provide references and enlightenments for guaranteeing the quality and safety of plant-based foods and promoting the healthy development of the plant-based food industry, this article systematically reviews and summarizes the potential chemical and biological safety risk factors of plant-based foods that are currently available on the market, and proposes possible solutions for the problems.